Public Interests in International Investment Law Balancing Protection for Investor and Environment - Ren, Qiang (Cambridge Scholars Publisher, 2018)
Are conflicts between the 'old capitalists' and 'new money' manifest in today's economy? Are investment treaties, which have traditionally been used to protect capital exporting states, now beginning to cause unwelcome side effects for them?International investment law has long been held as an economic and political instrument in the regime of international investment, with international investment treaties having been concluded to protect foreign investment and investors for a substantial period of time. However, the emerging new economic powers from the Third World are causing this to change. Taking the unique perspective of environmental protection in host states against states' obligations to protect and promote foreign investments under the existing international investment treaty practice and dispute settlement practices, this book examines this inescapable conflict. This is the first major work in this field to interpret investment treaty provisions by introducing environmental reflection. It offers proposals for rethinking and reshaping the current pro-investor international investment law through taking up broad environmental exceptions